Symposium - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1999)
"Symposium" by Plato is a Socratic dialogue written between 385-370 BC. At a banquet in ancient Athens, notable figures including Socrates, Alcibiades, and Aristophanes engage in a contest of speeches praising Eros, the god of love. Each man offers his perspective on love's nature and power$1 (Bfrom inspiring battlefield courage to transcending earthly desire. Through conflicting ideas and shifting viewpoints, the dialogue explores love's deepest meanings while showcasing both philosophical depth and literary artistry. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Symposium_(Plato)
Release date is 1999-01-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Socrates, 470 BC-399 BC; Philosophy, Ancient; Love -- Early works to 1800